AN EVALUATION ON THE IMPORTANCE OF POSITIVE PSYCHOLOGICAL CAPITAL - ÖZCAN, Gamze (Atlas Journal, 2021)
With the increase in competition in today's business environment and the widespread importance of the human element, which is the most important resource that businesses have in providing sustainable competitive advantage, employee productivity becomes more and more important every day and accordingly, new approaches are emerging in the field of organizational behavior. Positive organizational behavior approach, one of these approaches, has revealed the necessity for managers who always evaluate employees from a negative perspective, to evaluate them with a positive approach and to develop their positive psychological capital. The concept of "positive psychological capital", which offers a new perspective to organizations and is beyond human capital and social capital, consists of a combination of psychological capacities such as self-efficacy, hope, optimism and resilience. Its important effects on organizational behavior outcomes such as job performance, job satisfaction, organizational commitment and organizational citizenship behavior make it even more valuable to understand and work on positive psychological capital. In this study, it is aimed to make an evaluation on the importance and development of positive psychological capital for organizations. Understanding the components of psychological capital and the effects of these components and examining their importance for businesses will contribute to the research and development of the concept.